A systematic comparison of food intake data of the United States and the Netherlands for food allergen risk assessment. (April 2021) - Meima, Marie Y.; Blom, W. Marty; Westerhout, Joost; Kruizinga, Astrid G.; Remington, Benjamin C.; Houben, Geert F.
Abstract: National population-based food consumption surveys are used in food allergen risk assessment. It would be beneficial if food intake data is interchangeable between countries to bridge potential gaps present in national survey data, which is only possible when risk assessment outcomes for comparable food product groups between countries are fairly similar. Additionally, merged food intake data would enable risk assessments that cover scenarios for various countries, if based on the most critical situation. Therefore, we systematically compared risk assessment outcomes for a broad range of food groups based on United States and Dutch population food consumption survey data. We calculated risks for 14 allergenic foods for 9 concentrations (1-10, 000 ppm) to assess comparability. Depending on the assumed allergen concentration, risk assessment outcomes for 20% (10 out of 49) food groups differed considerably. We consider the number of potentially relevant risk differences too high to conclude that food intake data from the US and The Netherlands can be used interchangeably. To allow risk assessments that cover scenarios for several countries, we recommend development and use of a food intake dataset based on the highest intake levels for each food group of the involved countries to facilitate risk management efforts and harmonization. Highlights: Food allergen risks were compared using two population consumption surveys (US/NL). Risks were calculated for 14 allergens, 9 protein concentrations and 49 food groups. Risk assessment outcomes differed considerably for 10 out of 49 food groups (20%). Simulated risk levels differ too much to consider food intake data interchangeable. Development of a conservative, multi-country food intake dataset is recommended.